International differences in accounting practices under IFRS and the influence of the US - Lourenço, I. C.; Sarquis, R.; Branco, M. C.; Magro, N. (Australian Accounting Review, 2018)
This paper expands prior International Financial Reporting Standards (IFRS) accounting systems’ classifications to a broader set of 27 countries where IFRS adoption is a widespread practice, as well as the US. It examines the issue of whether a US model of accounting that includes countries which have adopted IFRS exists. The results suggest a classification distinguishing between three groups of countries based on the similarity of their accounting practices: 1) Australia and New Zealand; 2) US-influenced countries; and 3) South Africa, Oman and European countries. This study contributes to the literature not only by providing evidence of differences in accounting practices to a broader set of countries, but mainly by suggesting an economic explanation of the existence of accounting choices. In particular, economic proximity to the US may be an important factor influencing accounting practices in some countries, even after IFRS adoption.